Potensi Senyawa Metabolit Sekunder pada Tanaman Obat Sijukkot (Lactuca Indica L.) untuk Penanganan Penyakit Demam dengan Metode Molecular Docking - Sri Nanda; Ardi Mustakim (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
Sijukkot plants grow widely in the highlands of Lake Toba, the largest volcanic lake in the world. This plant, with the Latin name Lactuca indica L., grows abundantly in Dairi, Pakpak Bharat, Samosir and Humbang Hasundutan districts. Sijukkot has been proven to have made people in the Lake Toba area less susceptible to disease. Sijukkot contains many high chemical compounds in the roots, stems and leaves. For example glycosides, cardeolin, polyphenols, saponins, cardenolin, polyphenols, flavonoids and tannins. ( Molecular Docking ) is one of the simplest and most frequently used structure-activity based virtual methods. The purpose of this journal review is to determine the secondary metabolite compounds contained in the medicinal plant sijukkot to be developed as a fever reducer The research method used is a library study and literature review with the keywords molecular docking of secondary metabolite compounds of sijukkot as a medicinal plant to reduce fever, in the period 2020-2022. The results obtained were 5 secondary metabolite compounds which have potential as fever reducers and antioxidants. The conclusion is that ethanol extract and sijukkot leaves have high levels of phytochemicals which are good as formulations for fever medicine, antioxidant, antibacterial and can reduce sugar levels